Individual variation in the Neotropical salamander Bolitoglossa peruviana (Boulenger, 1883) (Amphibia: Plethodontidae) in eastern tropical Ecuador - Fugler, Charles M. (1979)
Bolitoglossa peruviana (Boulenger) (Amphibia: Urodela: Plethodontidae) was previously known from five reported individuals. The acquisition of 16 specimens from 10 km W Sucúa, valley of Río Upano, Province of Morona Santiago, Ecuador, permits the evaluation of the diagnostic morphometric characters, color and color pattern. Parameters of individual variation are tentatively defined.Bolitoglossa peruviana is poorly differentiated morphologically from other members of the altamazonica species group based on the variation encountered in the analysis of seven morphometric characters.